Hubungan Kadar Awal D-Dimer Terhadap Mortalitas pada Pasien COVID-19 Di RSUP Dr. Sardjito - Alqustar, Adam; Kurniawaty, Juni; Widyastuti, Yunita (Jurnal Komplikasi Anestesi, 2022)
In severe COVID-19 infection, the immune response can be exaggerated andcause a systemic cytokine storm that triggers systemic inflammatory responsesyndrome (SIRS). Excessive systemic inflammatory response can lead to systemicendothelial injury (endotheliopathy) and a hypercoagulable state that increasesthe risk of systemic macrothrombosis and microthrombosis. D-dimers arereleased when plasmin, a fibrinolytic enzyme, breaks down fibrin and is areflection of the endovascular thrombosis process. Assessment of circulating Ddimer concentrations is a sensitive test for diagnosing thrombotic status(including pulmonary embolism and DIC) and predicting mortality event inpatient contracted with COVID- 19